Therapeutic targeting of tumor hypoxia and necrosis with antibody α-radioconjugates. (5th November 2018) - Staudacher, Alexander H; Liapis, Vasilios; Brown, Michael P
ABSTRACT: Solid tumors are inherently difficult to treat because of large regions of hypoxia and are often chemotherapy- or radiotherapy-resistant. It seems that cancer stem cells reside in hypoxic and adjacent necrotic tumor areas. Therefore, new treatments that are highly selective for tumors and can eradicate cells in both hypoxic and necrotic tumor regions are desirable. Antibody α-radioconjugates couple an α-emitting radionuclide with the specificity of a tumor-targeting monoclonal antibody. The large mass and energy of α-particles result in radiation dose delivery within a smaller area independent of oxygen concentration, thus matching key criteria for killing hypoxic tumor cells. With advances in radionuclide production and chelation chemistry, α-radioconjugate therapy is regaining interest as a cancer therapy. Here, we will review current literature examining radioconjugate therapy specifically targeting necrotic and hypoxic tumor cells and outline how α-radioconjugate therapy could be used to treat tumor regions harboring more resistant cancer cell types.